2017
DOI: 10.1162/jocn_a_01115
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and Long-term Consequences of tDCS-augmented Cognitive Training

Abstract: Abstract■ A great deal of interest surrounds the use of transcranial direct current stimulation (tDCS) to augment cognitive training. However, effects are inconsistent across studies, and metaanalytic evidence is mixed, especially for healthy, young adults. One major source of this inconsistency is individual differences among the participants, but these differences are rarely examined in the context of combined training/stimulation studies. In addition, it is unclear how long the effects of stimulation last, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 64 publications
(89 reference statements)
4
63
0
1
Order By: Relevance
“…More recently, Au et al (2016) reported significant gains in verbal working memory after participants received tDCS over either left or right DLPFC. The same research team demonstrated that 12 months later, individuals who had initially received real tDCS, as opposed to sham, displayed substantial benefits to long-term retention (Katz et al, 2017). A possible mechanism underlying the long-term retention or relearning that we observed in both the left PFC and the M1 tDCS groups could involve plasticity-related protein synthesis.…”
Section: Tdcs Facilitates Consolidationmentioning
confidence: 62%
“…More recently, Au et al (2016) reported significant gains in verbal working memory after participants received tDCS over either left or right DLPFC. The same research team demonstrated that 12 months later, individuals who had initially received real tDCS, as opposed to sham, displayed substantial benefits to long-term retention (Katz et al, 2017). A possible mechanism underlying the long-term retention or relearning that we observed in both the left PFC and the M1 tDCS groups could involve plasticity-related protein synthesis.…”
Section: Tdcs Facilitates Consolidationmentioning
confidence: 62%
“…Reasons for this variance may be due to differences in the implemented protocols, individual reactions to exercise in general, as well as differences in baseline cognitive abilities and motivation to complete the tasks (36). This perhaps highlights the need for an initial cognitive test to measure baseline performance, so comparisons between the conditions can be made.…”
Section: Considerationsmentioning
confidence: 99%
“…However, although MCI patients scored higher in BDI compared to HE, the scores did not reach the threshold for clinical depression and may accordingly differ with respect to tonic cortical activation/excitation from depressed patients resulting in a different atDCS response. Moreover, since knowledge about confounders mostly stem from single session tDCS studies, it is largely unclear if and how individual differences of several (pathological) age-related changes such as cranial anatomy, functional connectivity, excitation/inhibition balance, psychological, and cognitive status affect both, cortical excitability and cognitive training independently and/or its combination [112]. Hence, a non-trivial, complex influence of inter-individual factors in response to multi-day tDCS seems likely.…”
Section: Variability Of Atdcs Effectsmentioning
confidence: 99%